The ICU guide for families : understanding intensive care and how you can support your loved one - Goitein, Lara, 1969- (Rowman & Littlefield, 2021)
"This book is for ICU patients' families, suddenly immersed in an alien and intimidating world. It clearly explains intensive care ranging from the details of the equipment and environment, to decisions about end-of-life care, focusing on how the reader can become an effective advocate for their loved one"--